2013
DOI: 10.1021/ja4114598
|View full text |Cite
|
Sign up to set email alerts
|

Strong Photon Energy Dependence of the Photocatalytic Dissociation Rate of Methanol on TiO2(110)

Abstract: Photocatalytic dissociation of methanol (CH 3 OH) on a TiO 2 (110) surface has been studied by temperature programmed desorption (TPD) at 355 and 266 nm. Primary dissociation products, CH 2 O and H atoms, have been detected. The dependence of the reactant and product TPD signals on irradiation time has been measured, allowing the photocatalytic reaction rate of CH 3 OH at both wavelengths to be directly determined. The initial dissociation rate of CH 3 OH at 266 nm is nearly 2 orders of magnitude faster than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 55 publications
4
64
0
4
Order By: Relevance
“…To further explore the possible charge/energy transfer processes in CH 3 OH photolysis, Xu et al measured the initial reaction rates of CH 3 OH photolysis on R‐TiO 2 (110) at 355 and 266 nm using the yield of dissociated H b atoms by detecting the recombinative desorption of the H 2 O product at a high temperature ( Figure ). The initial rate of CH 3 OH photolysis (or H 2 O formation) at 266 nm is much faster than at 355 nm by approximately two orders of magnitude, namely, the initial rate is strongly dependent on the irradiation wavelength (or photon energy).…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the possible charge/energy transfer processes in CH 3 OH photolysis, Xu et al measured the initial reaction rates of CH 3 OH photolysis on R‐TiO 2 (110) at 355 and 266 nm using the yield of dissociated H b atoms by detecting the recombinative desorption of the H 2 O product at a high temperature ( Figure ). The initial rate of CH 3 OH photolysis (or H 2 O formation) at 266 nm is much faster than at 355 nm by approximately two orders of magnitude, namely, the initial rate is strongly dependent on the irradiation wavelength (or photon energy).…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%
“…The unfilled squares indicate the rise times at 90% of the asymptotic values of the fits for both 355 and 266 nm photolysis. Reproduced with permission . Copyright 2013, American Chemical Society.…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%
“…10.4) [11,12], presumably because these events can sometimes be faster than thermalization [13]. A transfer to adsorbates of the phonon energy, which would be increased by thermalization, has also been suggested [12] and thought to possibly be capable of producing chemical changes.…”
Section: Charge Thermalizationmentioning
confidence: 99%
“…10.4) [11,12], presumably because these events can sometimes be faster than thermalization [13]. A transfer to adsorbates of the phonon energy, which would be increased by thermalization, has also been suggested [12] and thought to possibly be capable of producing chemical changes. A strong interaction of adsorbates with the TiO 2 surface, such as in the cases of 2-hydroxybenzoic acid [11] (with respect to aliphatic alcohols with long chains) [12], should obviously be favorable to these transfers of charge or energy.…”
Section: Charge Thermalizationmentioning
confidence: 99%
“…In particular, model surface science experiments have been conducted on the single crystal rutile TiO 2 (110) surface, under ultrahigh vacuum (UHV) and controlled coverage conditions. Experimentalists have characterized the electronic structure using ultraviolet, Xray, and two photon photoemission spectroscopy (UPS, XPS, and 2PP) [8][9][10][11][12][13][14][15], scanning tunnelling microscopy (STM) [14][15][16][17], and reaction products using temperature programmed desorption (TPD) [10,[18][19][20][21][22]. These experiments have shown that CH 3 OH can be photocatalytically dissociated on TiO 2 (110) to form CH 3 O and surface OH species [14,21], and selectively photooxidized to CH 2 O [19] and HCOOCH 3 [10,20].…”
Section: Introductionmentioning
confidence: 99%